COMPARATIVE ANALYSIS OF THE CUT-AND-COVER AND TOP-DOWN METHODS FOR BASEMENT CONSTRUCTION IN TERMS OF TIME AND COST ON THE WAHID HASYIM APARTMENT BUILDING PROJECT - Laia, Insyaf Maret; Naibaho, Pio Ranap Tua; Salim, Mohd Razman (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2025)
Basement structure work is a crucial part of constructing multi-story buildings, especially in dense urban areas with limited workspace or heavy equipment maneuverability. This study aims to analyze the comparison between two basement construction methods, namely the Cut-and-Cover method and the Top-Down construction method, using a case study on the Wahid Hasyim Apartment building project in Medan, North Sumatra. The analysis is based on two main parameters: execution duration and construction cost. The research findings indicate that the Cut-and-Cover method requires an execution time of 215 days with a total cost of Rp. 59,297,411,788.65. Meanwhile, the Top-Down method only requires an execution time of 164 days with a total cost of Rp. 48,012,728,671.13. Based on these results, the implementation of the Top-Down construction method is proven to be superior, with a time effectiveness of 23.72% and a cost efficiency of 19.03% compared to the Cut-and-Cover method. This is because with the Top-Down method, several work items can be performed concurrently.